2020
DOI: 10.1101/2020.11.26.390112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Red Wood Ants prefer mature Pine Forests in Variscan Granite Environments (Formica rufa-group)

Abstract: 0AbstractWe used presence/absence data of 5,160 red wood ant nests (RWA; Formica polyctena) acquired in a systematic large-scale area-wide survey in two study areas (≈350 ha) in the Oberpfalz, NE Bavaria, Germany to explore for the first time the influence of variable (e.g., forest type, tree age) and quasi-invariant factors (e.g., tectonics, geochemical composition of the bedrock) on nest size, spatial distribution and nest density for Variscan granites. A combination of the forest type (mature pine-dominated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…RWA nests were eight times more likely to be found within 60 m of known tectonic faults [12]. The results also showed that geogenic gases [13], rock formations with elevated Rn concentrations [14], fault-related CH4 emissions [15], volatile organo-halogens, alkanes and limonene [16] play key roles in the settlement of RWA nests. Physical phenomena such as tectonic stress variations in the subsurface, leading to highly mobile and oxidizing electronic charge carriers and formation of H2O2 that flow to the surface [17,18] may contribute to the survival of the colony.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…RWA nests were eight times more likely to be found within 60 m of known tectonic faults [12]. The results also showed that geogenic gases [13], rock formations with elevated Rn concentrations [14], fault-related CH4 emissions [15], volatile organo-halogens, alkanes and limonene [16] play key roles in the settlement of RWA nests. Physical phenomena such as tectonic stress variations in the subsurface, leading to highly mobile and oxidizing electronic charge carriers and formation of H2O2 that flow to the surface [17,18] may contribute to the survival of the colony.…”
Section: Introductionmentioning
confidence: 74%
“…Currently, Meinweg can be considered "no ants land" as no RWA nests have been observed so far. One reason could be that the concentrations of the soil gas anomalies were too low, for RWA especially prefer substrates with higher Rn concentrations [14] as observed at Meinweg. If the rifting process, the (re-)activation of faults and a higher concentrated degassing continue, RWA nests could be observed in this area in the future.…”
Section: Meinwegmentioning
confidence: 99%